Information Security and Cryptology 19th International Conference, Inscrypt 2023, Hangzhou, China, December 9-10, 2023, Revised Selected Papers, Part II - Ge, Chunpeng; Yung, Moti.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
The two-volume set LNCS 14526 and 14527 constitutes the refereed proceedings of the 19th International Conference on Information Security and Cryptology, Inscrypt 2023, held in Hangzhou, China, during December 9-10, 2023. The 38 full papers and 7 short papers presented in these proceedings were carefully reviewed and selected from 152 submissions. The papers have been organized in the following topical sections: Part I: Signature; blockchain; cryptography primitive; public key cryptography; security and privacy; Part II: System security; cryptography engineering; cryptanalysis; short papers, posters.
System Security: Text Laundering: Mitigating Malicious Features through Knowledge Distillation of Language Foundation Models -- An Android Malware Detection Method Using Better API Contextual Information -- TAElog: A Novel Transformer AutoEncoder-based Log Anomaly Detection Method -- EVFLR: Efficient Vertical Federated Logistic Regression Based on Batch Operation -- Clustered Federated Learning with Inference Hash Codes based Local Sensitive Hashing -- TIA: Token Importance Transferable Attack on Vision Transformers -- Cryptography Engineering: Hardware Acceleration of NTT-Based Polynomial Multiplication in CRYSTALS-Kyber -- V-Curve25519: Efficient Implementation of Curve25519 on RISC-V Architecture -- Cryptanalysis: Improved Integral Cryptanalysis of Block Ciphers BORON and Khudr -- Automatic Search of Linear Structure: Applications to Keccak and Ascon -- Differential-Linear Cryptanalysis of Round-Reduced SPARX-64/128 -- Improved Herrmann-May's Attack with Merging Variables and Lower LLL Bound -- Full Round Distinguishing and Key-Recovery Attacks on SAND-2 -- Real-time Symbolic Reasoning Framework for Cryptojacking Detection Based on Netflow-plus Analysis -- Non-malleable Codes from Leakage Resilient Cryptographic Primitives -- Short paper: DP-Loc: A Differential Privacy-Based Indoor Localization Scheme with Bilateral Privacy -- A Practical Multi-Candidate Voting Protocol on Quantum Blockchain Adapted for Various Tally Principles -- Quantum Augmented Lattice Attack on NTRU with Side Information -- Quantum Attacks: A View of Data Complexity on Offline Simon's Algorithm -- FaBFT: Flexible Asynchronous BFT Protocol Using DAG -- Forward Secure Online/offline Key Policy Attribute-based Encryption with Multi-keyword Search -- Differential Privacy Enhanced Dynamic Searchable Symmetric Encryption for Cloud Environments -- Poster: An Efficient Privacy-preserving Scheme for Weak Password Collection in Internet of Things -- TRGE: A Backdoor Detection after Quantizatio -- Improved Homomorphic Evaluation for Hash Function based on TFHE -- Power of Randomness Recovery: Tightly CCA-Secure KEM in the QROM -- Partial Key Exposure Attack on Common Prime RSA -- An Efficient Autonomous Path Proxy Re-Encryption without Pairing for Cloud-assisted mHealth.
Keywords: Data protection; Image processing -- Digital techniques; Computer vision; 9; Application software; Computer networks -- Security measures; Cryptography; Data encryption (Computer science).; Data and Information Security; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Communication Networks; Computer and Information Systems Applications; Mobile and Network Security; Cryptology